A snapshot of diversity: Intraclonal variation of Escherichia coli clones as commensals and pathogens - Marc Stegger; Rikke Fleron Leihof; Sharmin Baig; Raphael N. Sieber; Karen Rønø Thingholm; Rasmus L. Marvig; Niels Frimodt-Møller; Karen Leth Nielsen (Elsevier, 2020)
Whole-genome sequencing has enabled detailed studies on bacterial evolution during infection, but there is limited knowledge on intraclonal variation. In this study, we sought to provide a snapshot of the intraclonal diversity of Escherichia coli as both commensal in the faecal environment and pathogen during urinary tract infection, respectively. This was performed by whole-genome sequencing and analyses of single nucleotide polymorphisms (SNPs) and gene-content variation in ten isolates belonging to the same clone and isolated from rectal swabs or urine samples. We identified only one clone in eight of the nine urines sampled (89 %). In both the commensal and pathogenic state, the within-host diversity was limited with intraclonal SNP diversity of 0-2 non-synonymous SNPs for each clone. The genetic diversity showed variation in gene content in a range of 2-15 genes in total for all clones, including genes positioned on plasmids, and in the K- and O-antigen cluster. The observed SNP- and gene variation shows that sampling of one colony would be enough for surveillance, outbreak investigations and clonal evolution. However, for studies of adaptation during or between colonization and infection, this variation is relevant to consider.